Improvement of anthurium andreanum lind by in vivo and in vitro methods - Leena Ravidas (Department of Pomology and Floriculture, College of Horticulture, 2003)
Investigations on 'Improvement of Anthurium andreanum by in vivo and in vitro me thods ' were carried out at the Department of Pomology and Floriculture, College of Horticulture, Vellanikkara during the period from 1998 to 2001. The main objectives were to evolve new varieties of A. andreanum and to standardise the age of seed and media for in vitro seed culture. Six commercially important varieties of A. andreanum, VIZ., 'Nitta', 'Candy Queen', 'Lima', 'Red Dragon', 'Eureka Red', 'Agnihothri' and three species of Anthurium viz., A. crystallinum, A. ornatum and A. amnicola were selected for the study. Characterisation of the varieties was done morphologically which showed significa.n variations with respect to vegetative and floral characters. Year round flowering was obtained in all the varieties. The varieties 'Eureka Red' and 'Red Dragon' produced more number of spikes per year (8.9 and 8.0, respectively). Among the varieties, 'Candy Queen' produced the largest spathe (17.67 cm x 13.33 cm). Shortest spadix was observed in Red Dragon. Peduncle was straight in all the varieties except in 'Candy Queen'. The true flower of Anthurium is protogynous. The duration from spike appearance to unfurling ranged from 19.00 ,days in 'Lima' and 'Candy Queen' to 25.33 days in 'Agnihothri '. Female receptivity ranged from 12 days in 'Red Dragon' to 20.33 days in 'Eureka Red'. An interphase of 3 to 20 days was found in between female phase and male phase. Duration of male phase ranged from 9.33 days in 'Lima' to 20.67 days in 'Red Dragon'. Early ripening of seeds was obtained in 'Red Dragon' (145 days) while it took 208 days in 'Agnihothri'. Pollen grains of all the varieties were more or less round in shape. 'Agnihot hri' produced largest pollen grains (25.4 u). Pollen fertility was highest in A. crystallinum (69.8%). Pollen production was profuse during the period from June to October.